Penerapan Tema Arsitektur Tropis pada rancangan City Hotel Bintang Lima - Dita Suraiya (Jurnal Ilmiah Mahasiswa Arsitektur dan Perencanaan, 2020)
City Hotel is a commercially managed facility that provides lodging, food, beverage and other services, as well as providing supporting facilities primarily for business activities both nationally and internationally held in downtown hotels. Each Hotel has a particular theme to attract migrants. One of them is the Five Star City Hotel in Banda Aceh that uses the theme of Tropical Architecture for the comfort of the visitors and attracts their attention.Penorama tropical architecture theme in building of Five Star Hotel in Banda Aceh seen from exterior of building like orientation, facade, vegetation either in building or landscape, etc.Five Star City Hotel Building in Banda Aceh uses the theme of ArchitectureTropical by exploiting the potential and problems in nature and using materials from natural ingredients as much as possible.